Tanggung Jawab Pusat Kesehatan Masyarakat Pada Pelayanan Kesehatan Peserta Badan Penyelenggara Jaminan Sosial - Lusy Fradina; Hasbuddin Khalid; Muhammad Rinaldy Bima (Qawanin Jurnal Ilmu Hukum, 2020)
Health services at the first level are carried out by puskesmas in accordance with the regulation of the health social security administering body number 1 of 2014 concerning health insurance administrators. This study is to determine the responsibilities and inhibiting factors in the provision of health services, especially participants in social security administering bodies at the Watampone Health Center. This study uses an empirical method. The results of this study indicate that the responsibility of the Puskesmas Watampone in providing health services is legally responsible for all losses caused by negligence by medical and non-medical personnel at the Watampone Health Center. As for the inhibiting factors in the provision of health services at the Watampone Health Center in the form of facilities and infrastructure, inadequate human resources and financial management and utilization of funds from the social security administering bodies, they are not optimal.